Wisdom's law of watercourses. - Howarth, William; Jackson, Simon; Wisdom, A.S. (Allen Sidney); Wisdom, A.S. (Allen Sidney). (London : Sweet & Maxwell, 2011)
This work provides full coverage of the principles of common law on water rights and the statutory requirements relating to water management, water quality, and recreation and conservation.
Previous ed. published by Shaw in 1992. Earlier editions published as The law of rivers and watercourses.
Includes bibliographical references and index.
Keywords: Water -- Law and legislation -- England; Water -- Law and legislation -- Wales